Manufacturing, characterization, and application of nanoimprinted metallic probe demonstrators for electrical scanning probe microscopy - Jambreck, J. D.; Yanev, V.; Schmitt, H.; Rommel, Mathias; Bauer, A. J.; Frey, Lothar (Microelectronic Engineering, 2011)
For electrical scanning probe microscopy (SPM) techniques, tips with low electrical resistance nearly not being affected by probe wear out are desirable. High aspect ratio metal tips can fulfill these requirements. Nanoimprinted metallic probe demonstrators were manufactured on metal coated cantilevers by using UV nanoimprint lithography with a UV-curing resist containing silver particles, focused ion beam processing, and a micro-manipulator. The probes manufactured in this manner were electrically characterized, used in a SPM system for measurements, and compared with conventional probes. SPM experiments were performed in scanning capacitance microscopy mode (SCM), tunneling atomic force microscopy mode (TUNA), and topography atomic force microscopy mode. The demonstrator probes show a resistance which is lower than that of diamond coated probes and higher than that of metal coated probes. For the demonstrators, SCM maps with higher signal-to-noise ratio compared with standard probes were obtained. TUNA maps and local TUNA I-V-curves showed comparable results for Pt/Ir coated probes and the demonstrator probes. In topography mode the demonstrator tips show higher resolution than diamond coated tips and than silicon tips with a thicker Pt/Ir coating and lower resolution than silicon tips with a thin Pt/Ir coating.
Keywords: FIB; Metal tip; Nanoimprint lithography; Scanning probe microscopy; SCM; TUNA